Mom, I don't Want to go to School! - Luis Emilio Paniagua-Calvo (Universidad Nacional, Costa Rica, 2012)
This paper approaches the current reality of the Costa Rican secondary education system (7th to 11th grades). It brings up some weaknesses of the teaching-learning process in order to analyze the direction intended for the Costa Rican education. The conceptual approach is based on strategic-reflexive questions to facilitate the analysis of the current situation of the education centers, the direction the process is taking, the prevailing search for fairness and inclusion in education, and the improvement proposals. It concludes discussing the necessity of changing the traditional educational model into a transforming educational model addressed to the empowerment and freedom of the participants in the teaching-learning process. ms, emancipates, and frees the very same human beings involved in the teaching-learning process.